IMPLEMENTASI SWACAM DALAM MENINGKATKAN PELAYANAN PLN ULP BOJONEGORO - Jafar, Latifah Rukmiati Ifnu; Samsudin, Acep (Jurnal Bisnis Indonesia, 2024)
PLN ULP Bojonegoro Kota is a unit that focuses on customer service, handling various mattersrelated to electricity distribution, including electricity installation, bill payment, and othercustomer services. In collecting data, this research uses a qualitative method consisting ofobservation, interviews and documentation as well as theoretical studies, interviews wereconducted with employees of PLN ULP Bojonegoro The result of the research is that the SwaCamfeature is good enough and also very useful for PLN ULP Bojonegoro Kota customers in recordingkWh meters independently, however, socialization that has not been evenly distributed and thelack of public awareness of technological developments has resulted in there are still PLN ULPBojonegoro Kota customers who have not used the SwaCam feature. The SwaCam function in thePLN Mobile application will also have a positive impact on PLN customers and employeesbecause it is more efficient so that customers and employees can save time and energy in recordingkWh meters.Keywords : Implementation, SwaCam, Customer Service, PLN ULP Bojonegoro Kota.